Calcaneal apophysitis due to brucellosis - Ozgocmen, S; Kocakoc, E; Kiris, A; Sen, Y; Ardicoglu, O (Oxford Univ Press, 2003)
Brucellosis is still a major health problem in many geographical areas. Osteoarticular complications are important owing to their high prevalence.We report an unusual case of childhood brucellosis presenting with septic apophysitis of the calcaneus and abscess formation in a 12-year-old boy. The patient was successfully treated with a combination of antibiotics. The importance of early recognition of the disease and differential diagnosis is emphasized. Early recognition of infection, prolonged treatment, and long-term follow-up may improve the outcome.
Keywords: Children; Complications; Arthritis; Patient